BEYOND IMMERSION: THE EFFICACY OF VIRTUAL REALITY (VR) SIMULATIONS IN DEVELOPING TECHNICAL SKILLS FOR VOCATIONAL EDUCATION - Fauzi Erwis; Yang Xiang; Jari Koskinen (Yayasan Adra Karima Hubbi, 2025)
Traditional vocational education (VET) for complex psychomotor skills is costly, risky, and difficult to scale. While Virtual Reality (VR) is a potential solution, research has focused on “immersion,” not empirical “efficacy.” The critical gap is the unverified “transfer-of-training” from virtual simulations to real-world, physical tasks. This study aimed to empirically evaluate the efficacy of VR-only training versus traditional hands-on methods. It specifically sought to measure (1) “virtual-to-real” skill transfer, (2) long-term skill retention, and (3) training efficiency. An experimental pre-test/post-test/retention-test design was used. 80 (N=80) novice welding trainees were randomized to a VR-Only (n=40) or Traditional (n=40) group. Psychomotor skill was measured on physical equipment at baseline (T1), post-intervention (T2), and 4-week retention (T3) using an expert-validated rubric (PAR), analyzed with ANCOVA. The VR-Only group demonstrated statistically superior skill transfer on the physical post-test (T2) (p < .001, η_p^2 = .710). This superiority was durable, with significantly higher skill retention at the T3 follow-up (p < .001). The VR group also achieved competency 27% faster (6.4 vs 8.8 hours) and at zero consumable material cost. -fidelity VR, driven by instantaneous data-driven feedback, is a more effective, efficient, and cost-effective training modality than the traditional “gold standard” for novice psychomotor skill acquisition. This study provides robust validation for the “virtual-to-real” transfer-of-training.